Discovery of Anthophora onosmarum Morawitz, 1876 in Europe (Hymenoptera, Apidae) - Thomas J. Wood; Christophe J. Praz (Alpine Entomology)
Anthophora onosmarum is a poorly known bee species described from the Caucasus (Georgia). New fieldwork has revealed that the species is present in Bulgaria and Greece, and is also widespread across Turkey, predominantly on the Anatolian plateau. New behavioural data shows that A. onosmarum is likely narrowly oligolectic on the plant genus Onosma (Boraginaceae), and is capable of buzzing flowers to release pollen. This finding illustrates the growing trend of overlooked bee species with more Caucasian, Anatolian, or even Middle Eastern distributions occurring in under-surveyed mountainous parts of the Southern Balkans.